Protecting the Right of Non-Standard Workers to Equal Pay for Equal Work in Nigeria - Danesisi, R. A. (Unilag Journal of Humanities, 2019)
This paper examined the rights of non-standard workers to equal pay for equal work in the oil and gas industry in Nigeria. In particular it looked at a group of non-standard workers known as contract workers and analyses why they are discriminated against by employers. Workers in this form of work arrangement do not get equal pay for equal work of equal value as permanent employees. In Nigeria non-standard work arrangements have been growing steadily in the past 10 years but there is no legislation to regulate it. In the absence of regulation, most employers exploit these workers by not paying them what they pay to the permanent employees even though they perform same tasks and usually have the same skills as their permanent counterparts. The examination of the Nigerian labour law brought to fore the lack of provisions to regulate non-standard work arrangements and protect non-standard workers from exploitation. The paper concluded by advocating that the Nigerian legislature should amend the Labour Act so as to create a legal framework for the provision of equality in the workplace as has been done in other jurisdictions such as Ghana, South Africa, China, United States, Australia and the European Union.